Effect of Watering Time and Liquid Organic Fertilizer Concentration on the Growth and Production of Shallots (Allium Ascalonicum L.) - Panataria, Lince Romauli; Saragih, Meylin Kristina; Sitorus, Efbertias (ITScience (Information Technology and Science), 2024)
Shallot production in Indonesia has not been able to meet market needs due to the scarce availability of subsidized chemical fertilizers. Another alternative to replacing chemical fertilizers can be using Liquid Organic Fertilizer. The aim of this research was to determine the effect of watering time and concentration of liquid organic fertilizer on the growth and production of shallots (Allium ascalonicum L.). The design in this study was a Randomized Block Design (RAK), consisting of 2 treatment factors, namely watering time (W) consisting of 2 treatment levels, namely: W1= 1x1 week, W2= 1x2 weeks and POC concentration (P) consisting of 4 treatment levels namely: P1= 2 ml/240 ml water/plant, P2= 4 ml/240 ml water/plant, P= 6 ml/240 ml water/plant and P4= 8 ml/240 ml water/plant. Data analysis uses analysis of variance, if the treatment factor has a significant effect on the variance test, a mean difference test is carried out using the Duncan Multiple Range Test (DMRT) at 5% level. The results showed that POC watering time had a significant effect on tuber diameter and number of tubers per sample, but had no significant effect on fresh weight of tubers per sample and dry weight of tubers per sample. POC concentration had a significant effect on tuber diameter, number of tubers per sample, fresh weight of tubers per sample and dry weight of tubers per sample.